Interoperability engine design for model sharing and reuse among OpenMI, BMI and OpenGMS-IS model standards. (October 2021) - Zhang, Fengyuan; Chen, Min; Kettner, Albert J.; Ames, Daniel P.; Harpham, Quillon; Yue, Songshan; Wen, Yongning; Lü, Guonian
Abstract: Owing to the heterogeneity of geo-analysis models, many scholars and researchers have designed and promulgated standards in an attempt to address this. However, models based on different standards still cannot be shared and reused easily among different model frameworks. For example, models based on the OpenMI, BMI and OpenGMS-IS standards have heterogeneous development styles and formats, so they cannot interoperate. This article analyses the challenges faced when sharing and reusing models across different standards and provides a solution for model interoperation among them. By mapping fields, converting functions, and reorganizing components, our "interoperability engine" allows models that use one standard to be operated within a framework that supports a different standard. This article discusses the developed interoperability method and provides case studies (using e.g. SWMM, FDS, and the Permamodel Frost Number component) to successfully demonstrate model interoperation. Highlights: Model interoperation among OpenMI, BMI, and OpenGMS-IS. Sharing and reuse models across different standards. Providing a solution for engine design of model interoperation. Strategies for fields, functions, and components converting among standards.